Managing the uncertainty of occupant behaviour for building energy evaluation and management - Naylor, Sophie (2018)
The influence of building occupancy and user behaviour on energy usage has been identified as a source of uncertainty in current understanding of operational buildings, and yet it is rarely directly monitored. Gathering data on the occupancy of buildings in use is essential to improve understanding of how energy is used relative to the actual energy requirements of building users.